A Methodology to Secure ATM System Using Microcontroller - Ankita S. Ugare,; Anuja S. Bhendavade,; Mayuri L. Patil,; Monika R. Varnole,; Swati S. Halunde, (Journal of Electronic Design Engineering, 2019)
This paper gives the depiction of the new way to deal with wards the security of ATM (Automatic Teller Machine) Systems. Frauds related to the ATM (Automatic Teller Machine) are increasing day by day which is a serious issue. ATM security is used to provide protection against these frauds. Though security is provided for ATM machine, cases of robberies are increasing. Past advancements give security inside machines to secure transaction, yet machine isn't flawlessly ensured. The ATM machines are not safe since security provided traditionally were either by using RFID reader or by using security guard outside the ATM. This security is not sufficient because RFID card can be stolen and can be misused for robbery as well as watchman can be black mailed by the thief. So there is a need to propose new technology which can overcome this problem. This paper proposes a system which aims to design real-time monitoring and controlling system.